OP0315 Reasons for discontinuation of biological agents in patients with juvenile idiopathic arthritis: data from the portuguese register, reuma.pt. (15th June 2017) - Mourão, AF; Eusébio, M; Melo-Gomes, J; Oliveira-Ramos, F; Martins, F; Estanqueiro, P; Salgado, M; Guedes, M; Conde, M; Carvalho, S; Tavares-Costa, J; Duarte, C; et al.
Abstract : Background: Persistence on medication mainly reflects both effectiveness and safety of a drug. Understanding the reasons to stop bDMARD in routine clinical practice can help to better define the efficacy and safety of biologic medications in children with juvenile idiopathic arthritis (JIA). Objectives: To investigate persistence on treatment and the reasons for discontinuation of the first biological in patients with JIA. Methods: Portuguese patients with JIA registered in Reuma.pt who started a bDMARD were analyzed. Persistence was defined as the time between treatment initiation and discontinuation of the first bDMARD. The mean time until discontinuation was calculated using Cox regression survival estimates and the reasons for discontinuation of the first bDMARD were registered. Results: Of the 1724 JIA patients registered in Reuma.pt, 319 received biological therapy, 62% (198) female. The mean age at disease onset was 7.7±4.8 years and the mean time between the beginning of JIA and the first bDMARD was 8.2±9.4 years. The mean disease duration was 13.7±10.7 years and the mean age at the beginning of biological therapy was 15.8±9.4 years. The distribution of JIA subtypes was: 19.1% polyarticular RF-negative, 17.2% enthesitis-related arthritis, 16.6% polyarticular RF-positive, 16% extended oligoarticular, 13.5% persistent oligoarticular, 12% systemic JIA and 0.9% had undifferentiated arthritis. Considering the whole group, 53.2% have had extra-articular manifestations and 18.4% have or had had uveitis since the beginning of the disease. Persistence on treatment, before discontinuation (due to any cause) was 34.7 months (range: 0.03–182 months) adjusted for gender, biological therapy, JIA subtype, age at the beginning of biological therapy, and disease duration until initiating first bDMARD. The major reasons for drug discontinuation was inefficacy (49.6%), remission (14.2%), adverse events (10.6%), patient decision (1.6%) and pregnancy planning (1.4%). In 22.7% the reason was not specified. Conclusions: Almost half of the JIA patients stop the first biological agent, due to lack of response, reinforcing the need for the existence of several treatment options fully studied in JIA. Disclosure of Interest: None declared